2011
DOI: 10.1007/s11356-011-0501-9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of patterns, levels, and trends of perfluorinated compounds in aquatic organisms and bird eggs from representative German ecosystems

Abstract: Generally, PFC levels were lower in marine than in freshwater biota. PFC burdens were higher in biota from the ESB-North Sea sites than in Baltic Sea organisms. Levels of PFC were quite high especially in top predators of both limnetic and marine ecosystems. Only low PFC levels were detected in eggs of terrestrial birds. A decrease of PFOS levels from maximum values around the year 2000 observed at least in North Sea biota may be a result of a production cease and shifts in marketing pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Interestingly, when we compared these with our statistical analyses (Additional file 7, Figures S8-S10) we found 11 datasets showing clearly diverging results (tawny owl [11], polar bear (Ittoqqortoormiit) [124], beluga (Cook Inlet) [123], polar bear (Barrow) [132], herring [139], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80], Mellum-3 sets [80,105,128]). In eight cases, our statistical analyses resulted in insignificant trends, with low power to detect a trend, whereas the authors found significantly decreasing trends in seven (tawny owl [11], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80]), herring gull (Mellum-3 datasets [80,105,128]) and significantly increasing trends in one of these datasets (polar bear, Barrow [132]). For one dataset (polar bear (Ittoqqortoormiit [124]), our results showed no significant trends on either side of the change point but statistically significantly higher concentrations after the change point, whereas the authors found a significant increasing trend before the change point and significant decreasing trend after.…”
Section: Biological Samplesmentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, when we compared these with our statistical analyses (Additional file 7, Figures S8-S10) we found 11 datasets showing clearly diverging results (tawny owl [11], polar bear (Ittoqqortoormiit) [124], beluga (Cook Inlet) [123], polar bear (Barrow) [132], herring [139], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80], Mellum-3 sets [80,105,128]). In eight cases, our statistical analyses resulted in insignificant trends, with low power to detect a trend, whereas the authors found significantly decreasing trends in seven (tawny owl [11], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80]), herring gull (Mellum-3 datasets [80,105,128]) and significantly increasing trends in one of these datasets (polar bear, Barrow [132]). For one dataset (polar bear (Ittoqqortoormiit [124]), our results showed no significant trends on either side of the change point but statistically significantly higher concentrations after the change point, whereas the authors found a significant increasing trend before the change point and significant decreasing trend after.…”
Section: Biological Samplesmentioning
confidence: 97%
“…The muscle data will be discussed here as there were more time points available for this tissue compared to liver. Herring gulls from three colonies (Heuwise, Mellum, Trischen) on the German coast have also been the subject of three separate studies ( [80,105,128]). Again, these are built on the same material by adding more samples and extending the time period studied.…”
Section: Biological Samplesmentioning
confidence: 99%
See 3 more Smart Citations